Oral supplementation with bovine colostrum (intactÔ ) improves rowing performance in elite female rowers - Buckley, J. D.; Brinkworth, G. D.; Bourdon, P. C.; Gulbin, J.; Stilwell, E. J.; David, A.; Myers, N. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Bovine colostrum is secreted by cows during the first few days after calving and is a rich source of bioactive components, including growth factors. The present study employed a double-blind, placebo controlled, parallel, randomised design to determine the effect of supplementation with a low fat, low lactose, concentrated bovine colostrum protein powder (intact™, NorthField Laboratories Pty Ltd) on rowing performance in a group of elite female rowers. 8 female rowers from the South Australian Sports Institute (Age 15-21 years), completed a 9 week training program whilst consuming 60 g/day of intact™ bovine colostrum powder (CP, n=3) or whey protein powder (WP, n=5). All subjects consumed their normal diets and kept food diaries throughout the study period. Subjects completed 2 x 4-step rowing tests (ROW1 and ROW2) at weeks 0 and 9, consisting of 3 x 4 min sub-maximal loads and 1 x 4 min maximal effort. ROW1 and ROW2 were separated by 15 minutes of recovery. There were no differences in dietary intake (P>0.05) or training volumes (P>0.05) between the two groups during the study period. The distances covered (m) and work done (kJ) during the submaximal work loads were the same in both groups at weeks 0 and 9 (P>0.91) and during the 4 min maximal efforts at week 0 (P>0.05). There were greater increases in the distance covered (CP, 33.7 ± 2.3 m, WP, 23.2 ± 2.3 m; P=0.05) and work done (CP, 6.3 ± 0.1 kJ, WP, 4.2 ± 0.4 kJ; P=0.004) during the 4 min maximal effort of ROW1 in CP by week 9. Buffer capacity was also higher in CP by week 9 (P=0.02). Distance covered (P=0.03) and work done (P=0.05) during the 4 min maximal effort of ROW2 also increased more in CP. These results indicate that oral supplementation with intact™ bovine colostrum improves rowing performance in elite female rowers.